Biological control of rigidoporus microporus the cause of white root disease in rubber using PGPRs in vivo - Mathurot Chaiharn (2020)
© 2019, Chiang Mai University. All rights reserved. White root disease caused by Rigidoporus microporus is abundant in Hevea brasiliensis plantations in Thailand. Disease control by systemic fungicides is expensive, pollutes the environment and causes health hazards. Plant growth-promoting rhizobacteria (PGPRs) obtained from rubber growing areas were screened for antagonistic activity against R. microporus. In the present study, 120 strains of Actinomycetes and 98 strains of fluorescent pseudomonad were screened for antagonistic traits as siderophore, β-1,3-glucanase, chitinase, cellulase, catalase and antifungal activity, in vitro. On the basis of dual culture assays, Lac 19, Lac 17 and LBR 14 strains were selected based on their bioactive compound-producing activities which included catalase, chitinase and cellulase. According to cell wall composition analysis and 16S rRNA homology, these strains were identified as Streptomyces seoulensis Lac 19, Streptomyces malaysiensis Lac 17, and Streptomyces ahygroscopicus LBR 14, respectively. Application of biocontrol agents, S. malaysiensis Lac 17 and S. ahygroscopicus LBR 14, in nursery stage of H. brasiliensis showed greater suppression of the disease in the same level as hexaconazole. The application of selected Streptomyces would be an alternative for the control of R. microporus in the long-term rubber plantation.